OPTIMALISASI PERTANIAN ORGANIK MELALUI PENGGUNAAN MOL di KAMPUNG LIKINO DISTRIK HUBIKIAK, KABUPATEN JAYAWIJAYA - Anti Uni Mahanani (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Jayawijaya is one of the regions in the Papua Highlands Province that implements organic farming, but agriculture in this region still employs traditional farming methods, which do not incorporate additional inputs into cultivation techniques. Without additional inputs, soil nutrients are indirectly depleted and depleted. The solution to addressing nutrient deficiencies in the cultivation techniques used in the Jayawijaya region is the addition of organic fertilizer. One such addition is the addition of Local Microorganisms (MOL). The main objective of this community service activity is: 1) The understanding and awareness of the people in Likino village regarding the importance of adding nutrients to the soil and plants through the provision of MOL can be increased; 2) Provide skills to the community about making and utilizing MOL as an environmentally friendly organic fertilizer. The implementation of activities using extension methods to the community. The conclusion of this activity is that the community can understand and be aware of the importance of providing input to plants by providing MOL and the community, especially farmers in Likino village, can become able and skilled in making and applying MOL as an environmentally friendly organic fertilizer.